Ethnic Fermented Foods and Alcoholic Beverages of Asia - Tamang, Jyoti Prakash (Springer India : Imprint: Springer, 2016)
Asia has a long history of preparation and consumption of various types of ethnic fermented foods and alcoholic beverages based on available raw substrates of plant or animal sources and also depending on agro-climatic conditions of the regions. Diversity of functional microorganisms in Asian ethnic fermented foods and alcoholic beverages consists of bacteria (Lactic acid bacteria and Bacillus species, micrococcii, etc.), amylolytic and alcohol-producing yeasts and filamentous moulds. Though there are hundreds of research articles, review papers, and limited books on fermented foods and beverages, the present book: Ethnic Fermented Foods and Alcoholic Beverages of Asia is the first of this kind on compilation of various ethnic fermented foods and alcoholic beverages of Asia. This book has fifteen chapters covering different types of ethnic fermented foods and alcoholic beverages of Asia. Some of the authors are well-known scientists and researchers with vast experiences in the field of fermented foods and beverages who include Prof. Tek Chand Bhalla, Dr. Namrata Thapa (India), Prof. Yearul Kabir and Dr. Mahmud Hossain (Bangladesh), Prof. Tika Karki (Nepal), Dr. Saeed Akhtar (Pakistan), Prof. Sagarika Ekanayake (Sri Lanka), Dr. Werasit Sanpamongkolchai (Thailand), Prof. Sh. Demberel (Mongolia), Dr. Yoshiaki Kitamura, Dr. Ken-Ichi Kusumoto, Dr. Yukio Magariyama, Dr. Tetsuya Oguma, Dr. Toshiro Nagai, Dr. Soichi Furukawa, Dr. Chise Suzuki, Dr. Masataka Satomi, Dr. Kazunori Takamine, Dr. Naonori Tamaki and Dr. Sota Yamamoto (Japan), Prof. Dong-Hwa Shin, Prof. Cherl-Ho Lee, Dr. Young-Myoung Kim, Dr. Wan-Soo Park Dr. Jae-Ho Kim (South Korea) Dr. Maryam Tajabadi Ebrahimi (Iran), Dr. Francisco B. Elegado (Philippines), Prof. Ingrid Suryanti Surono (Indonesia), Dr. Vu Nguyen Thanh (Vietnam). Researchers, students, teachers, nutritionists, dieticians, food entrepreneurs, agriculturalist, government policy makers, ethnologists, sociologists and electronic media persons may read this book who keep interest on biological importance of Asian fermented foods and beverages.